Ethical and Statistical Considerations in Models of Moral Judgments - Sivill, Torty (Frontiers in Robotics and AI, 2019)
This work extends recent advancements in computational models of moral decision making by using mathematical and philosophical theory to suggest adaptations to state of the art. It demonstrates the importance of model assumptions and considers alternatives to the normal distribution when modelling ethical principles. We show how the ethical theories, utilitarianism and deontology can be embedded into informative prior distributions. We continue to expand the state of the art to consider ethical dilemmas beyond the Trolley Problem and show the adaptations needed to address this complexity. The adaptations made in this work are not solely intended to improve recent models but aim to raise awareness of the importance of interpreting results relative to assumptions made, either implicitly or explicitly, in model construction.